EDUKASI BRAND KE KONSUMEN MELALUI DIGITAL MARKETING (STUDY BRAND INSTO DALAM PROGRAM #BUKA MATA BUKA INSTO) - Dwi Nurul Prihantono (Jurnal Akrab Juara, 2019)
Maintaining the existence of a brand is not an easy job, it requires creative communication strategies so that the products will always have good awareness therefore they are always remembered by consumers. For this reason, brand education is very important so that the consumers can get information and understanding about the products, especially for a specific health product such as insto. The development of the digital world which is progressing rapidly, makes the Insto brand develops and utilizes digital marketing as a communication strategy in educating its consumers. This study used a qualitative research method where the result of this study showed that digital marketing is an effective and interesting communication strategy in educating the consumers, thus the consumers are able to know and understand about the product, how to get the product and how to use the product.